Penegakan Hukum terhadap Adanya Aksi Persekusi - I Made Arif Dwi Cahyadi; I Gusti Bagus Suryawan; I Nyoman Sutama (Fakultas Hukum Universitas Warmadewa, 2019)
Legal issues against the presence of the action of the persecution in the community growing and complex, so it needs a regulation which expressly regulate and make the legal umbrella to protect the community itself for the apparatus law enforcement easy doing the application of penalties against the existence of the action for the persecution. Until this time the rule of law-related persecution in Indonesia have not been clearly arranged according to where the large Indonesian Language Dictionary of persecution that is is arbitrary against a hunt or a number of citizens and being hurt, compounded or the Chief. From the background of the above, the authors take the title research law enforcement Action Against the existence of Persecution. Formulation of the problem in this research, namely how the concept of persecution in positive law and how the law enforcement action against the existence of persecution. The type of research used in the writing of this thesis is the normative legal research. Normative research type that is based on the rule of law in order to answer the problems that exist. The concept of persecution in positive law are examined, namely the Constitution of the Republic of Indonesia year of 1945, the legislation of the Republic of Indonesia Number 39 Year 1999 on human rights and the Criminal law. Law enforcement by the police against the existence of the rule of law to use the persecution of action contained in the legislation of criminal law.